Height of Mining-Induced Fractured Zones in Overlying Strata and Permeability of Rock with Nonpenetrative Fractures - Yu Liu; Qimeng Liu; Wenping Li; Youbiao Hu (Geofluids)
Exploitation of shallow thick coal seams that are overlain by phreatic aquifers may cause loss of the water resource and destruction of the surface ecological environment. In order to explain the phenomenon that the actual leakage of phreatic water is greater than the predicted value, field investigation and analogue simulation were carried out, and the nonpenetrative fractured zone (NFZ) was proposed based on the original three zone theory. Further, a “vertical four-zone model” was established and the overlying strata was divided into a caved zone (CZ), through-going fractured zone (TFZ), NFZ, and continuous zone (COZ) from the bottom to the top. The characteristics of fractured rock within NFZ and the determination method of its height were studied. The results showed that the height of NFZ ranged from 11.55 to 21.20 m, which was approximately 0.17 times the combined height of the TFZ and the CZ. To reveal the mechanism of phreatic water leakage, the permeability of rock within NFZ was studied for their premining and postmining using an in situ water injection test and laboratory test. The results showed that the permeability of the rock in NFZ was increased by 7.52 to 48.37 times due to mining, and the magnitude of the increase was nonlinear from top to bottom. The increase of permeability of tested specimens was also related to the lithology. The results of the study are helpful to the prediction of the potential loss of phreatic water and the determination of the mining thickness.